Research on the coordinated optimization of energy storage and renewable energy in off-grid microgrids under new electric power systems - Zhuoran Song; Mingli Zhang; Yuanying Chi; Jialin Li; Yi Zheng (Global Energy Interconnection)
The supply of electricity to remote regions is a significant challenge owing to the pivotal transition in the global energy landscape. To address this issue, an off-grid microgrid solution integrated with energy storage systems is proposed in this study. Off-grid microgrids are self-sufficient electrical networks that are capable of effectively resolving electricity access problems in remote areas by providing stable and reliable power to local residents. A comprehensive review of the design, control strategies, energy management, and optimization of off-grid microgrids based on domestic and international research is presented in this study. It also explores the critical role of energy storage systems in enhancing microgrid stability and economic efficiency. Additionally, the capacity configurations of energy storage systems within off-grid networks are analyzed. Energy storage systems not only mitigate the intermittency and volatility of renewable energy generation but also supply power support during peak demand periods, thereby improving grid stability and reliability. By comparing different energy storage technologies, such as lithium-ion batteries, pumped hydro storage, and compressed air energy storage, the optimal energy storage capacity configurations tailored to various application scenarios are proposed in this study. Finally, using a typical microgrid as a case study, an empirical analysis of off-grid microgrids and energy storage integration has been conducted. The optimal configuration of energy storage systems is determined, and the impact of wind and solar power integration under various scenarios on grid balance is explored. It has been found that a rational configuration of energy storage systems can significantly enhance the utilization rate of renewable energy, reduce system operating costs, and strengthen grid resilience under extreme conditions. This study provides essential theoretical support and practical guidance for the design and implementation of off-grid microgrids in remote areas.